2018
DOI: 10.1016/j.econmod.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Dividend policy of Indonesian listed firms: The role of families and the state

Abstract: We investigate factors influencing the dividend policy of the listed Indonesian firms by focusing on agency costs and ownership structure. Our study finds that firms with higher conflicts of interest among managers and shareholders pay lower dividends. In the context of the conflicts of interest among major and minor shareholders, we find that such conflicts would exert little impact on dividend payments. Further, we find that the family-controlled firms prefer to pay less dividends whereas the corporations wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 72 publications
(133 reference statements)
10
53
0
9
Order By: Relevance
“…Kuzucu (2015) and Yıldız et al (2014) analyzed the firm-specific factors affecting the dividend decisions and they both used panel data for the period from 2006 to 2013 and from 2003 to 2010 respectively by utilizing panel regression. His finding confirms the result of Duygun et al (2018) and Al-Najjar and Kilincarslan (2016), and he also found the size and age positively affect the dividend payout. Yıldız et al (2014) found liquidity, size and profitability have a positive impact on the dividend payout.…”
Section: Literature Reviewsupporting
confidence: 75%
“…Kuzucu (2015) and Yıldız et al (2014) analyzed the firm-specific factors affecting the dividend decisions and they both used panel data for the period from 2006 to 2013 and from 2003 to 2010 respectively by utilizing panel regression. His finding confirms the result of Duygun et al (2018) and Al-Najjar and Kilincarslan (2016), and he also found the size and age positively affect the dividend payout. Yıldız et al (2014) found liquidity, size and profitability have a positive impact on the dividend payout.…”
Section: Literature Reviewsupporting
confidence: 75%
“…This is because foreign investors are rational individuals and select firms that pay higher dividends. Duygun et al (2018) noted that there is no relationship between foreign investors and the payment of dividends in firms. Against this inconclusive result in literature, the fourth hypothesis is stated as follows:…”
Section: Non-executive Directors and Dividend Payout Structurementioning
confidence: 99%
“…Third, the natural logarithm of total assets was included in the model to control for firm size. This is because large firms tend to pay high dividends (Duygun, Guney, & Moin, 2018;Fama & French, 2001;Tahir & Mushtaq, 2016;Yusof & Ismail, 2016), since large firms can obtain external finance at an overall lower rate than their small counterparts.…”
Section: Control Variablesmentioning
confidence: 99%